Research methods identifying correlation between physical environment of schools and educational paradigms / Mokyklų fizinės aplinkos ir ugdymo nuostatų sąsajų tyrimai - Grėtė Brukštutė (Mokslas: Lietuvos Ateitis, 2016)
The article is analysing the research that was already carried out in order to determine correlation between a physical environment of schools and educational paradigms. While selecting materials for the analysis, the attention was focused on studies conducted in the USA and European countries. Based on these studies the methodological attitudes towards coherence of the education and spatial structures were tried to identify. Homogeneity and conformity of an educational character and a physical learning environment became especially important during changes of educational conceptions. The issue how educational paradigms affect the architecture of school buildings is not yet analysed in Lithuania, therefore the results of this research could actualize a theme on correlation between educational paradigms and the architecture of school buildings and form initial guidelines for the development of the modern physical learning environment.